Bisphosphonate-associated Osteonecrosis of the Jaws: a Survey of the Level of Knowledge of Dentists about the Risks of Bisphosphonate Therapy - Hristamyan-Cilev Meri A.; Pechalova Petya P.; Raycheva Ralitsa D.; Hristamyan Veselka P.; Kevorkyan Ani K.; Stoilova Yordanka D. (Folia Medica, 2019)
Introduction: Bisphosphonate-associated osteonecrosis of the jaws (BAONJ) is a side effect of treatment with bisphosphonate (BP). Reports of this complication have increased recently.